The more centralized the spatial structure is, the greater the economic growth? Evidence from urban agglomerations in western China - Jing Zhao; Na Chen; Zhen Jin (Humanities & Social Sciences Communications)
Abstract This research examines data from eight urban agglomerations in western China from 2003 to 2020 to investigate the impacts of spatial structure changes on economic growth. Using dynamic spatial econometrics, we find that spatial agglomeration has significant effects on the economic growth performance of urban agglomerations in western China. Moreover, the direct effects of three indicators measuring spatial structure—population, industry and land use spatial structure—on economic growth are all directly positive. Moreover, these three spatial structure indicators affect economic growth through mediating variables such as environmental pollution, technological progress, and industrial structure. Further heterogeneity tests reveal that the positive effects of spatial structure on economic growth are increasing and that the positive effects expand from the short term to both the short and long term.